The road to evolutionary success: insights from the demographic history of an Amazonian palm - Melo, Warita A.; Freitas, Cintia G.; Bacon, Christine D.; Collevatti, Rosane G. (Heredity, 2018)
Evolutionary success, as demonstrated by high abundance and a wide geographical range, is related to genetic variation and historical demography. Here we assess how climatic change during the Quaternary influenced the demography and distribution of the Neotropical swamp palm Mauritia flexuosa. Using microsatellite loci and coalescent analyses we examined how demographical dynamics affected genetic diversity, effective population size and connectivity through time and space. Mauritia flexuosa presents significant genetic differentiation between the Amazonian and Cerrado biomes and among different river basins. Amazonian lineages are ancient compared to lineages from the Cerrado, a pattern corroborated using the fossil pollen record, where the species was absent from the Cerrado during the cold and dry periods of the last glacial cycles, then returned during the wet, interglacial phases. Coalescent simulations show that the pattern of observed genetic diversity for M. flexuosa is most likely due to a range retraction during the Last Glacial Maximum, leading to multiple refugia and resulting in high differentiation between Amazonian and Cerrado biomes. Isolation-by-distance and by-environment also shaped the distribution and evolutionary success of M. flexuosa. Our study provides new insights into the historical factors that affected geographical distribution and structure genetic diversity, contributing to long-term evolutionary success.